Binders and mixing process in stabilization and solidification of copper slag - Pham, Huy Phuong. (2008)
Land disposal regulations are becoming more stringent as a result of health, economic and political concerns. To the largest extent practicable, alternatives to land disposal are always desirable, such as through waste minimization, recycling and destruction, e.g. incineration. However, not all wastes can be recycled due to technical or economic difficulties. Besides, the incineration residue has highly toxic concentration and can not be disposed of without further treatment. In such cases, stabilization and solidification (S/S) technologies are a viable option. Basically, the S/S technologies involve waste containment within a solid matrix using different binder materials such as cement, pozzolans, clay and polymer. This study was undertaken with the aim to study the feasibility of converting copper slag into construction materials using S/S technology. The effect of copper slag on concrete performance like workability, compressive strength, porosity as well as heavy metal leaching was investigated in order to assess the feasibility of practical application for concrete products. The results revealed that the compressive strength of the copper slag-concrete increased as copper slag replacement ratio increased. TCLP showed that cement mortar was successful in encapsulating heavy metals. Hence, it is safe to use copper slag as sand replacement in concrete for normal construction. mEP indicated that leaching of copper and barium could be a potential problem if the concrete is subjected to severe leaching conditions.